IMPLEMENTASI PROGRAM BANTUAN SOSIAL BAGI PENUNGGU PASIEN DI KABUPATEN BADUNG - Ananda, I Wayan Meidita; Winaya, I Ketut; Wismayanti, Kadek Wiwin Dwi (CITIZEN CHARTER, 2020)
ABSTRACT The Badung Regency Social Service is a government agency as the executor of regional autonomy which deals with social issues, particularly performing a role in improving the quality of health services. One of them is the Social Assistance Program for Patient Companions. The research objective to be achieved is to determine the extent of the Implementation of the Social Assistance Program for Patient Companions in Badung Regency The results of this study indicate that the Implementation of the Social Assistance Program for Patient Companions has already reached the target performance well, but it cannot be said to be the maximum results.be seen from the lack of community understanding patterns regarding social assistance programs for patient companion in Badung Regency. Therefore, awareness is needed from both the social services and the community to maintain good communication with each other so that the aims and objectives can be achieved optimally. Keywords: Implementation of Social Assistance Programs, Patient Companions, Social Services.